Difference of Gain and Loss on Currency Translation and Conversion - Thu Trang; Nguyen Van Su (Journal La Bisecoman, 2020)
This article discusses the advantages and disadvantages of translation and conversion of currency. Foreign currency translation is the process of reporting financial information from one currency to another. Foreign currency transactions take place on the spot, forward, or swap markets. Currencies bought or sold on the spot generally have to be delivered as soon as possible, that is, within 2 working days. Foreign currency translation is carried out to prepare joint financial reports. Translation is simply a change in monetary units, just as a balance sheet expressed in British pounds is restated into its US dollar equivalent. No physical exchange takes place, and no related transaction occurs as if a conversion were made.